2015
DOI: 10.14814/phy2.12348
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed shear stress reduces Klf2 expression in arterial-venous fistulae in vivo

Abstract: Laminar shear stress (SS) induces an antiproliferative and anti-inflammatory endothelial phenotype and increases Klf2 expression. We altered the diameter of an arteriovenous fistula (AVF) in the mouse model to determine whether increased fistula diameter produces disturbed SS in vivo and if acutely increased disturbed SS results in decreased Klf2 expression. The mouse aortocaval fistula model was performed with 22, 25, or 28 gauge needles to puncture the aorta and the inferior vena cava. Duplex ultrasound was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 45 publications
4
11
0
Order By: Relevance
“…In ECs exposed to unidirectional flow, we observed, as expected, cell alignment and actin fiber orientation with flow direction, while in those exposed to reciprocating flow EC shape remained cuboidal with only peripheral cytoskeletal organization. In line with previous investigations by other groups (26, 27), we confirmed significant expression of KLF-2 in ECs exposed to unidirectional pulsatile flow, while cell exposure to reciprocating flow did not induce KLF-2 expression. Of interest, in ECs exposed to unstable and reciprocating flow we observed an increase in MCP-1 and IL-8 expression (24).…”
Section: The Presence Of Disturbed Flow Patterns In Avfsupporting
confidence: 93%
“…In ECs exposed to unidirectional flow, we observed, as expected, cell alignment and actin fiber orientation with flow direction, while in those exposed to reciprocating flow EC shape remained cuboidal with only peripheral cytoskeletal organization. In line with previous investigations by other groups (26, 27), we confirmed significant expression of KLF-2 in ECs exposed to unidirectional pulsatile flow, while cell exposure to reciprocating flow did not induce KLF-2 expression. Of interest, in ECs exposed to unstable and reciprocating flow we observed an increase in MCP-1 and IL-8 expression (24).…”
Section: The Presence Of Disturbed Flow Patterns In Avfsupporting
confidence: 93%
“…In line with other investigations available in literature (13,18,72,78), our present results confirmed that EC expression of mRNA coding for KLF2 was significantly increased by cell exposure to UND WSS. At the same time, this flow condition induced a decrease in the mRNA expression of PLD1, ITGA4, and RASA1.…”
Section: H55supporting
confidence: 93%
“…In the vascular endothelium, KLF2 has been widely studied; it is upregulated in high laminar unidirectional shear stress (physiological conditions) and downregulated in low oscillatory shear stress (pathophysiological conditions) (35,128,137). In extensive in vitro experiments, human aortic valve endothelial cells (HAVECs) from noncalcified aortic valves exhibited higher KLF2 expression in high unidirectional shear stress (20 dynes/cm 2 , conditions similar to ventricularis) and lower expression in low and oscillatory shear stress (-5 dynes/cm 2 , conditions similar to fibrosa), reflecting the fact that the ventricularis side shows higher KLF2 expression and an antiinflammatory phenotype (50).…”
Section: Kruppel-like Factorsmentioning
confidence: 99%